Paediatric single mitochondrial DNA deletion disorders: an overlapping spectrum of disease. Issue 3 (29th October 2014) - Broomfield, Alexander; Sweeney, Mary G.; Woodward, Cathy E.; Fratter, Carl; Morris, Andrew M.; Leonard, James V.; Abulhoul, Lara; Grunewald, Stephanie; Clayton, Peter T.; Hanna, Michael G.; Poulton, Joanna; Rahman, Shamima
Abstract: Background: Single large‐scale mitochondrial DNA (mtDNA) deletions (SLSMDs) are amongst the most frequently diagnosed mtDNA disorders in childhood, yet their natural history remains poorly understood. We report the natural history of a large multicentre cohort of such children. Methods: We reviewed case notes from three different UK centres to determine the clinical course of 34 patients (16 female, 18 male) with childhood‐onset mitochondrial disease caused by SLSMDs. Kaplan–Meier analysis was used to compare survival of patients presenting with haematological features (Pearson syndrome) and those with nonhaematological presentations. Results: The most frequent initial presentation was with isolated ptosis (16/34, 47 %). Eleven (32 %) patients presented with transfusion‐dependent anaemia soon after birth and were diagnosed with Pearson syndrome, whilst ten were classified as having Kearns–Sayre syndrome, three as having progressive external ophthalmoplegia (PEO) and seven as having PEO‐plus. Three patients did not conform to any specific mitochondrial syndrome. The most frequently affected organ during the disease course was the kidney, with documented tubular or glomerular dysfunction in 17 of 20 (85 %) cases who had detailed investigations. SLSMDs were present in blood and/or urine cells in all cases tested, indicating that muscle biopsy is not necessary for diagnosis in the paediatric age range. Kaplan–Meier survival analysis revealed significantly worse mortality in patients with Pearson syndrome compared with the rest of the cohort. Conclusions: Mitochondrial disease caused by SLSMDs is clinically heterogeneous, and not all cases conform to a classical mitochondrial syndrome. Multisystem disease is the norm, with anaemia, renal impairment and endocrine disturbance being the most frequent extraneurological features. SLSMDs should be considered in the differential diagnosis of all children presenting with ptosis.